Analisis Hubungan Antara Sikap, Norma Subyektif, Dan Kontrol Keperilakuan Yang Dirasakan Terhadap Perilaku Berbagi Pengetahuan Manajer: Studi Empiris Pada Perusahaan Di Wilayah Jakarta - Frans Warmanto; Handhika Noviant Thenu (Universitas Multimedia Nusantara, 2009)
Managers have shown an increasing interest in understanding and encouraging knowledge sharing behaviour in their organizations. However, very few empirical studies have examined managers’ perceptions of knowledge-sharing behaviour. This study used Ajzen’s theory of planned behaviour (TPB) to develop and test a research model to assess the factors that influence encouragement of knowledge-sharing intention and behaviour by managers. The data from a survey of managers in Jakarta were used empirically to test the proposed research model. A self-administered questionnaire was distributed to respondents by the drop-off/pick-up method, resulted 150 respondents. Moreover, confirmatory factor analysis (CFA) was conducted to examine the reliability and validity of the measurement model, and the structural equation modelling (SEM) technique was used to evaluate the research model. The analytical results showed that the research model fitted the data well and the main determinants of enterprise knowledge-sharing behaviour were the encouraging intentions of managers. Additionally, managers’ attitudes, subjective norms and perceived behavioural control were found to positively influence intentions to encourage knowledge sharing. Finally, research and practical implications were suggested. Keywords: Knowledge management, Perception, managers, Behaviour, Modelling